Eksperimen Semu Permainan Ular Naga Modifikasi Terhadap Kemampuan Menulis Anak di Taman Kanak-kanak - Farsyofmi, Engla Ventara; Wirman, Asdi (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
Writing ability is one of children's language skills that needs to be developed from an early age. Improving writing skills can be done using an interesting game in the form of a modified dragon snake game. The dragon snake game, modifying some of the steps or how to play it, can improve aspects of language development such as writing and can also attract children's interest in learning activities. The aim of this research was to find out the influence of the modified dragon snake game on children's writing abilities at the Padang II State Kindergarten. This research approach uses a quantitative method with a Quasi Experimental method. The data collection technique uses tests, namely a series of questions and exercises to measure the child's abilities. The research subjects were 20 samples of group B children at Kindergarten II Padang consisting of 10 experimental class children and 10 control children. The data analysis technique used in this research uses the t test. Before carrying out the t test, prerequisite tests are carried out, namely the normality test and homogeneity test. The results of research data analysis show that the data is normally distributed and homogeneous. Furthermore, based on the t-test, it shows the Sig value. (2-tailed) is 0.042 < 0.05, so H0 is rejected, Ha is accepted, meaning that there is an average difference between the pre-test and post-test which has increased in score so it can be concluded that the modified dragon snake game has an effect on writing ability. in early childhood.